Risk factors for mortality over 18 years in 317 ICUs in 9 Asian countries: the impact of healthcare-associated infections - Rosenthal, Victor Daniel; Jin, Zhilin; Rodrigues, Camilla; Myatra, Sheila Nainan; Divatia, Jigeeshu Vasishth; Biswas, Sanjay K.; Shrivastava, Anjana Mahesh; Kharbanda, Mohit; Nag, Bikas; Mehta, Yatin; Sarma, Smita; Todi, Subhash Kumar; et al. (Cambridge University Press, 2023)
Objective: To identify risk factors for mortality in intensive care units (ICUs) in Asia.